Energy Saving Analysis of Data Center Air Conditioning System Based on Application of Natural Cooling Technology - L; Jixiang; Wang Tiejun; Zhao Li; Wang Jinghui; Hu Liwen; Liu Guanghui (Zhileng xuebao)
In order for better selection and energy saving design of data center air conditioning system, energy consumption models for three types of data center air conditioning, air cooling direct expansion unit, dual cooling source chiller and combined refrigeration unit with heat pipe, were established. The annual energy efficiency ratio (AEER) and annual energy consumption of the three types of air-conditions with the same air conditioning load and return air parameters were calculated and analyzed based on the meteorological data of four cities, i.,e., Harbin、Beijing, Shanghai and Guangzhou in DEST,. The results showed that the AEER of these three units increase along with the decrease of the average temperature from south to north. As a result, the AEER of them are 4.07-4.45、4.00-6.84 and 4.27-8.20. Comparing the combined refrigeration unit with heat pipe with air cooling direct expansion unit and dual cooling source chiller, the energy saving rate of the heat pipe is 4.8%-46% and 6.4%-16.6% respectively. In comparison with the air cooling direct expansion unit, the energy saving of dual cooling source unit are obvious, because it can use natural cooling resource to replace or partially replace the compression refrigeration. Compared with dual cooling source chiller, combined refrigeration unit with heat pipe has the advantages of low refrigerant transporting power, high heat exchange efficiency and anti-freezing. Therefore, combined refrigeration unit with heat pipe is the first choice for the data center air conditioning system in low annual temperature area.